A FORUM FOR CONSTRUCTIVE PUBLIC DISCOURSE: A NEEDS ANALYSIS - Richard Miles (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The recent prevalence of various AI tools and online platforms has digitized how L2 learners approach learning English in higher education. Learners can now easily access not only language support online but can also share their ideas and voice their opinions on a range of platforms. With more opportunities to interact online, instead of the more traditional transactional usage of language tools, learners need to be prepared for how to express themselves and how to deal with feedback. Current research has largely focused on medical forums when analyzing the posting of Japanese higher education learners. Before constructing a public forum for English language learners in Japanese higher education to share their voices on a host of opinions and issues, a needs analysis study was conducted to assess what online tools and platforms language learners currently utilize, what they learn from their experiences, and how they would like to shape future interactions and platforms. A survey was carried out with 150 first-year university students anonymously, online, and in English. Semantic analysis (Liu, 2022) was employed to draw out pertinent findings, along with a modified version of Chun, Kern, and Smith’s (2016) framework for analysis. Findings suggest that learners are typically passive with their interactions on public forums, but a sizable minority seek to learn more about being more involved in public discourse. This presentation will detail the study’s findings and discuss how they will shape the creation of a forum for constructive public discourse aimed at Japanese university students.